Pengaruh Dewan Gereja Sedunia Terhadap Gereja-Gereja Anggotanya - Febron Manik; Meditatio Situmorang (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
The World Council of Churches (DGD) has played an important role in facilitating unity among its member churches since its founding in 1948. Through the ecumenical movement, the DGD encouraged churches to participate in social and spiritual issues, especially post-World War II. The organization strengthens solidarity between denominations, helps churches face modern challenges, and advocates for social justice and peace. With its broad membership, the DGD is a forum for churches to unite in a common mission for the glory of God.